Професор Лідія Дунаєвська та фольклористика у Київському національному університеті імені Тараса Шевченка - Шурко, Л. (Народна творчість та етнографія, 2007)
This article is dedicated to the life and work of the well-known Ukrainian folklorist Lidiya Dunayevska, who died in 2006. She was a folklorist, literary critic, the specialist in the tale studies and the history of Ukrainian folkloristics. In this article scholarly work of Prof. Dunayevska, who for a long time was a head of the Department of the Folkloristics in Kyiv State University, is analyzed through the field work, publications, social and scientific life of her department.